Effect of relative humidity and pre-annealing temperature on spin-coated zinc tin oxide films made via the metal–organic decomposition route. Issue 32 (28th July 2017) - Son, Y.; Liao, A.; Peterson, R. L.
Abstract : Solution-processed zinc tin oxide thin-film transistor using metal–organic decomposition achieves wide process window in terms of ambient humidity during deposition. Abstract : Here we investigate the effect of relative humidity and pre-annealing temperature on multi-layer, solution-processed amorphous zinc tin oxide films formed by metal–organic decomposition (MOD). We show that changing the pre-annealing temperature can significantly change the metal stoichiometry and hydroxide content of zinc tin oxide films. Films pre-annealed at higher temperatures exhibit tin-rich, hydroxide-poor compositions and enhanced thin-film transistor performance, with an increase in field-effect mobility from 0.75 cm 2 V −1 s −1 to 5.91 cm 2 V −1 s −1 and a decrease in subthreshold voltage swing from 1.37 V decade −1 to 0.44 V decade −1 . In contrast to conventional sol–gel methods, our solution-processed thin-film transistors made via the MOD route exhibit uniform performance over a wide range of process conditions. Intentional, controlled variation of relative humidity (RH) during film deposition from 10% RH to 83% RH results in little change in electron mobility (3.76 to 5.62 cm 2 V −1 s −1 ) or subthreshold swing (0.23 to 0.39 V decade −1 ). The uniformity of film properties over a wide process window indicates the utility of the MOD approach for producing high-quality solution-processed semiconductors for large-area and printed electronics.